Case Report: Rapid Treatment of Uridine-Responsive Epileptic Encephalopathy Caused by CAD Deficiency - Zhou, Ling; Deng, Jie; Stenton, Sarah L.; Zhou, Ji; Li, Hua; Chen, Chunhong; Prokisch, Holger; Fang, Fang (Frontiers in Pharmacology, 2020)
We present two unrelated Chinese patients with CAD deficiency manifesting with a triad of infantile-onset psychomotor developmental delay with regression, drug-refractory epilepsy, and anaemia with anisopoikilocytosis. Timely translation into uridine supplementation, within 2-month of disease onset, allowed us to stop conventional anti-epileptic drugs (AEDs) and led to dramatic improvement in the clinical symptoms, with prompt cessation of seizures, resolution of anaemia, developmental progress, and prevention of development of severe and non-reversible manifestations. The remarkable recovery and prevention of advanced disease with prompt treatment, highlights the need to act immediately upon genetic diagnosis of a treatable disease. This further reinforces CAD deficiency as a treatable neurometabolic disorder and emphasises the need for a biomarker or genetic new born screening for early identification.